Neurological activation during verbal fluency task and resting-state functional connectivity abnormalities in obsessive-compulsive disorder: a functional near-infrared spectroscopy study - Qiao, Yongjun; Song, Xiaohui; Yan, Jin; Pan, Wenxiu; Chia, Chinhsuan; Zhao, Dan; Niu, Chuanxin M.; Xie, Qing; Jin, Haiyan (Frontiers in Psychiatry, 2024)
Objective.This study aims to investigate the activation of frontotemporal functional brain areas in patients with Obsessive-Compulsive Disorder(OCD) during a Verbal Fluency Task(VFT), and to compare their brain functional connectivity in a resting state with that of healthy controls. The goal is to deepen our understanding of the neuropathological mechanisms underlying OCD. Methods.32 patients with OCD and 32 controls matched for age, gender, handedness, and years of education participated in this study, they were divided into OCD group and healthy comtrol group. We conducted VFT task tests and 10-minute resting state tests on both groups by using functional Near-Infrared Spectroscopy(fNIRS). The VFT was utilized to assess the activation(beta values) and the integral and centroid values of the frontal and bilateral temporal lobes, including brain areas BA9 and 46(dorsolateral prefrontal cortex), BA10(frontal pole), BA45(inferior frontal gyrus), BA21(middle temporal gyrus), and BA22(superior temporal gyrus). We evaluated the functional connectivity levels of these areas during the resting state. Differences in these measures between OCD patients and healthy controls were analyzed using two-sample independent t-tests and non-parametric Mann-Whitney U tests. Results.During VFT, OCD had smaller integral values(z=5.371, p<0.001; t=4.720, p<0.001), and larger centroid values(t=-2.281, p=0.026; z=-2.182, p=0.029) compared to healthy controls, along with a reduced number of activated channels detected by fNIRS. Additionally, activation values(β) in various functional brain areas, including BA9, BA46, BA10, BA45, BA21, and BA22, were significantly lower in the OCD group(all p< 0.01). In the resting state, notable disparities in functional connectivity were observed between the inferior frontal gyrus(IFG) and dorsolateral prefrontal cortex(DLPFC) in the OCD group, in comparison to the control group. Specifically, there was a significant increase in connectivity between the left IFG and right DLPFC, suggesting the presence of altered connectivity patterns in these areas. Conclusions.The study highlights significant disparities in neural activation and functional connectivity between OCD patients and healthy controls during VFT. Specifically, reduced activation was noted in the frontal and bilateral temporal lobes of OCD patients, alongside alterations in resting-state functional connectivity between the IFG and DLPFC. These findings contribute to our understanding of the neurobiological underpinnings of OCD and may guide future therapeutic strategies.